2019
DOI: 10.1155/2019/2897867
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Activity of Leersia hexandra Sw. (Poaceae) Aqueous Extract on Ethanol-Induced Hypertension in Wistar Rat

Abstract: Leersia hexandra (L. hexandra) is used in traditional medicine to treat many diseases including hypertension. This study aimed to evaluate the curative effects of the aqueous extract of L. hexandra on hypertension. Hypertension was induced in rats by oral administration of ethanol (5 g/kg/day) for five weeks. The animals were divided into 2 groups: one group of 5 rats receiving distilled water (10 mL/kg) and another group of 20 rats receiving ethanol. At the end of the 5 weeks of administration of ethanol, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…However, in hypertensive rats treated with 1 per cent of flaxseed compared to those of untreated rats, the catalase enzymatic activity in heart and that of GSH-Px in heart and aorta was restored, suggesting that the efficacy of this extract may be partially attributed to its capacity to improve antioxidant status. Our results are in agreement with those of Bilanda et al (2019), who showed that the treatment with Leersia hexandra ( L. hexandra ) prevents oxidative stress in endothelial dysfunction caused by ethanol consumption.…”
Section: Discussionsupporting
confidence: 93%
“…However, in hypertensive rats treated with 1 per cent of flaxseed compared to those of untreated rats, the catalase enzymatic activity in heart and that of GSH-Px in heart and aorta was restored, suggesting that the efficacy of this extract may be partially attributed to its capacity to improve antioxidant status. Our results are in agreement with those of Bilanda et al (2019), who showed that the treatment with Leersia hexandra ( L. hexandra ) prevents oxidative stress in endothelial dysfunction caused by ethanol consumption.…”
Section: Discussionsupporting
confidence: 93%
“…Measurements. Blood pressure (BP) and heart rate (HR) of LNHR were recorded by invasive method under anesthesia (1.5 g/kg intraperitoneal injection of urethane) according to a method previously described [16]. e trachea was exposed and intubated to facilitate spontaneous respiration.…”
Section: Blood Pressure and Heart Ratementioning
confidence: 99%
“…However, its abuse is a public health problem [ 6 ]. Several studies have shown that chronic heavy alcohol consumption most often causes liver, gastrointestinal, nerve, and cardiovascular damages leading to physiological dysfunction [ 7 , 8 ]. It has been clearly established that chronic ethanol consumption leads to increased blood pressure and thus hypertension.…”
Section: Introductionmentioning
confidence: 99%